The impact of religion extremism phenomena on the community’s coexistence : (2003-2020 Kurdistan region- Iraq as an example) - Waleed Jaafar Ibrahim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The research was conducted through many interviews, analysis of several documents, and the use of books, journals, and academic publications using electronic libraries and the Internet. Additionally, the study uses a content analysis type method to achieve its objectives. In essence, the study aims to draw attention to religious extremism and how it affects how communities coexist in the Kurdistan Region. It also tries to illustrate the level of extremism in the Kurdistan Region. The study confirms that religious extremism is a global phenomenon and poses a serious threat to coexistence, especially in multi-communal societies. The Kurdish society is a multi-ethnic society, so it is likely to be exposed to the threat of religious extremism. The study also presents a picture of the ways in which religious extremism occurs, as well as the motives and obstacles facing this phenomenon. It also indicates how favorable the Kurdistan Region is for the emergence and development of this phenomenon. Finally, the study concludes that extremism exists in all societies but in varying proportions. In the Kurdistan Region, this phenomenon is not seen as a threat to the coexistence of different communities. If there is, it is at such a low level that it is not worth mentioning, because any mention is likely to be exaggerated, illogical, or used for other purposes, such as political ones. Until now, there have been no cases of extremism against religious minorities that have threatened this long-standing coexistence. of course, this has not happened easily. There have been many reasons and motives, for example, the role of the government and the religious men. These are strengthening factors to prevent the emergence and development of religious extremism in the Kurdistan Region.